2007
DOI: 10.1007/s10899-007-9057-5
|View full text |Cite|
|
Sign up to set email alerts
|

Perceived Availability, Risks, and Benefits of Gambling among College Students

Abstract: The current study was an exploration of gambling-related perceptions and their relation to gambling behavior among young adult college students. Three hundred and two ethnically diverse undergraduates at a large urban public university completed a survey to assess their perceptions of the availability, risks, and benefits of gambling, and the South Oaks Gambling Screen (SOGS) to assess gambling behavior and problems. Participants generally rated gambling as more available than alcohol or marijuana, and less ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 35 publications
4
24
0
Order By: Relevance
“…This is of concern, as perceiving benefits from gambling has a significant positive relationship with problem gambling among college students (Wickwire et al, 2007). Research examining college students' motivation for gambling has found that money, enjoyment, social contact, and excitement were the top reasons for gambling (Neighbors, Lostutter, Cronce, & Larimer, 2002).…”
Section: Expectanciesmentioning
confidence: 99%
“…This is of concern, as perceiving benefits from gambling has a significant positive relationship with problem gambling among college students (Wickwire et al, 2007). Research examining college students' motivation for gambling has found that money, enjoyment, social contact, and excitement were the top reasons for gambling (Neighbors, Lostutter, Cronce, & Larimer, 2002).…”
Section: Expectanciesmentioning
confidence: 99%
“…Whereas some studies (e.g., LaBrie, Shaffer, LaPlante, & Wechsler, 2003;Slutske, Jackson, & Sher, 2003) indicate that the college student population might have a lower percentage of gamblers than the general population, others indicate the percentage is similar or higher (e.g., Wickwire et al, 2007;Winters, Bengston, Door, & Stinchfield, 1998). However, research has indicated that college students who gamble are more likely to do so at a disordered level (Blinn-Pike, Lokken Worthy, & Jonkman, 2007;Shaffer & Hall, 2001).…”
mentioning
confidence: 99%
“…A third of the 419 participants had taken part in gambling activities in the previous month. While a large majority of youth had not gambled in the previous month, 21.2% took part in gambling activities on a weekly or daily basis, a proportion higher than that found in studies among 18-to-25-year-old university students (between 4% and 18.5%) [7,10,22,55]. Furthermore, 11.9% had spent between $100 and $5000, which is a considerable sum considering the living conditions of these youth.…”
Section: Discussionmentioning
confidence: 83%